Contribution of wastewater-based epidemiology to SARS-CoV-2 screening in Brazil and the United States. (15th February 2023) - Henriques, Taciane Barbosa; Cassini, Servio Túlio; de Pinho Keller, Regina
Abstract: Wastewater-based epidemiology (WBE) is a valuable tool for investigating the existence, prevalence, and spread of pathogens, such as SARS-CoV-2, in a given population. WBE, proposed as part of the SARS-CoV-2 surveillance strategy for monitoring virus circulation, may complement clinical data and contribute to reducing the spread of the disease through early detection. In developing countries such as Brazil, where clinical data are scarce, information obtained from wastewater monitoring can be crucial for designing public health interventions. In the United States, the country with the largest number of confirmed SARS-CoV-2 cases worldwide, WBE programs have begun to be carried out to investigate correlations with coronavirus disease 2019 (COVID-19) clinical data and support health agencies in decision-making to prevent the spread of the disease. This systematic review aimed to assess the contribution of WBE to SARS-CoV-2 screening in Brazil and the United States and compare studies conducted in a developed and developing country. Studies in Brazil and the United States showed WBE to be an important epidemiological surveillance strategy in the context of the COVID-19 pandemic. WBE approaches are useful for early detection of COVID-19 outbreaks, estimation of clinical cases, and assessment of the effectiveness of vaccination program. HIGHLIGHTS: Early alert of SARS-CoV-2 through the use of wastewater-epidemiology strategies. Wastewater surveillance can complement clinical data to provide a tool of surveillance SARS-CoV-2 circulation. Wastewater monitoring could help identify the presence of asymptomatic individuals in the community. Contribution of WBE to decision-making in public policies. Contribution of WBE to the health system.